Constraining Stroke Order During Manual Symbol Learning Hinders Subsequent Recognition in Children Under 4 1/2 Years - Merritt, Emily; Swain, Shelley N.; Vinci-Booher, Sophia; James, Karin H. (Frontiers in Psychology, 2020)
In the age of technology, writing by hand has become less common than texting and keyboarding. Learning letters by hand however, has been shown to have profound developmental importance. One aspect of writing by hand that has been understudied is the effect of learning symbols stroke-by-stroke, a dynamic action that does not occur with keyboarding. We trained children to draw novel symbols in either an instructed stroke order or in a self-directed stroke order and tested: 1) whether learning novel symbols in a specified stroke order benefits subsequent recognition more than learning in a self-directed stroke order, 2) whether seeing novel symbols unfold in the stroke order that was taught would aid in recognition, and 3) whether any effects are age-dependent. Our results demonstrate that producing a symbol with a self-directed stroke order benefits symbol recognition in children younger than 4.5 years of age relative to instructed stroke orders, but not in children older than 4.5 years. Further, when instructed to draw a symbol in a particular way, seeing the strokes appear in the learned stroke order does not benefit recognition. These results stress the importance of allowing children to produce symbols in a self-directed manner and, by extension, that constraining how a child learns to write can adversely affect subsequent recognition.